1998
DOI: 10.1001/archpsyc.55.11.967
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of Abuse of Different Drugs in Men

Abstract: Background: Previous research has demonstrated genetic and environmental influences on abuse of individual substances, but there is less known about how these factors may influence the co-occurrence of abuse of different illicit drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
210
2
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 657 publications
(227 citation statements)
references
References 35 publications
14
210
2
1
Order By: Relevance
“…Nonetheless, our finding is consistent with twin data suggesting that most drug use disorders share a common genetic diathesis (Kendler, et al, 2003, Tsuang, et al, 1998. If that is true, it seems reasonable to posit that members of SUD families share an underlying trait that may be indexed by psychopathological or associated cognitive features.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Nonetheless, our finding is consistent with twin data suggesting that most drug use disorders share a common genetic diathesis (Kendler, et al, 2003, Tsuang, et al, 1998. If that is true, it seems reasonable to posit that members of SUD families share an underlying trait that may be indexed by psychopathological or associated cognitive features.…”
Section: Discussionsupporting
confidence: 89%
“…Family, twin, and adoption studies indicate that genes play a significant etiologic role in the development of substance use disorders (SUDs) (Cloninger, 1987, Luthar and Rounsaville, 1993, Merikangas, et al, 1985, Mirin, et al, 1986, Pickens, et al, 1991, Rounsaville, et al, 1991, Tsuang, et al, 1998. Although these studies have led to the widely accepted conclusion that much of the familial transmission of SUDs is due to genes, the specific genes involved have been difficult to detect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on work documenting genetic contributions to antisocial and substance-use behaviors (e.g. Lyons et al 1995 ;Tsuang et al 1998 ;Jacobson et al 2002 ;Kendler et al 2006 ;Torgersen et al 2008), at least three separate research groups have reported evidence for a hierarchal account of the genetics of the externalizing spectrum. In this model, much of the genetic effect on substance dependence (alcohol and illicit substances) and antisocial (conduct disorder and antisocial personality) DSM disorders is in common, yet there are also smaller (but not trivial) residual genetic effects on substance dependence (Young et al 2000 ;Krueger et al 2002 ;Kendler et al 2003).…”
Section: Geneticsmentioning
confidence: 99%
“…In comparison to most addictive substances, the vulnerability of heroin abuse appears to have a significant genetic load (6). Several genetic variations of the human MOR gene (OPRM1) have been identified.…”
mentioning
confidence: 99%